Modifikasi bahan ajar mata pelajaran sekolah dasar bermuatan gizi seimbang dan makanan jajanan anak sekolah - Almira Sitasari; Weni Kurdanti; Lastmi Wayansari (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Fighting malnutrition should also target school-aged children and adolescents. Development of teaching materials containing nutrition education could be alternative for structured intracurricular education in schools. Objective: To modified elementary school teaching materials and develop teaching tool with nutrition content. Partners: Partners are teaching staff at SDN Kembangjitengan 2 Balecatur Yogyakarta, school that located in the Nutrition Awareness Village (Assisted Village) of Poltekkes Kemenkes Yogyakarta. Methods: Development of teaching materials and learning tools with nutrition content following the DeSPIS framework by fulfilling the supply of education materials containing nutrition education. Results: The development of teaching materials containing  education about balanced nutrition and snack foods for school children can be done in teaching materials of grade 1 and grade 5. Importance: This community service can help elementary school teaching staff to educate students regarding balanced nutrition and snack foods for school children in a structured manner in the intracurricular learning program.